Discovering computers complete - Shelly, Gary B.; Cashman, Thomas J. ;Vermaat, Misty E. (Boston, Massachusetts : Thomson Course Technology, 2009)
DISCOVERING COMPUTERS 2008: COMPLETE, INTERNATIONAL EDITION delivers students an unparalleled learning experience by offering the most current and comprehensive information on computers and technology.
1. Introduction to Computers. Special Feature: Timeline 2008.2. The Internet and World Wide Web. Special Feature: Making Use of the Web.3. Application Software.4. The Components of the System Unit.5. Input. Special Feature: Personal Mobile Devices.6. Output. Special Feature: Digital Imaging and Video Technology.7. Storage.8. Operating Systems and Utility Programs. Special Feature: Buyer's Guide 2008.9. Communications and Networks.10. Database Management.11. Computer Security, Ethics, and Privacy. Special Feature: Computer Forensics.12. Information System Development.13. Programming Languages and Program Development.14. Enterprise Computing. Special Feature: Enterprise Order Processing: A Case Study.15. Computer Careers and Certification. Special Feature: Digital Entertainment. Appendices .A: Coding Schemes and Number Systems. B: Quiz Yourself Answers. C: Computer Acronyms.
Includes bibliographical references and index.
Keywords: COMPUTER NETWORKS